Beyond the Law: A Review of Knowledge, Attitudes and Perceptions in ADA Employment Research - Gould, Robert; Parker Harris, Sarah; Caldwell, Kate; Fujiura, Glenn; Jones, Robin; Ojok, Patrick; Enriquez, Katherine Perez (Disability Studies Quarterly, 2015)
The Americans with Disabilities Act (ADA, 1990) is the cornerstone of civil rights policy for people with disabilities. Although enforced through the justice system, the legacy of the ADA transcends well beyond its legal ramifications. The policy’s framework and the rhetoric of Disability Rights suggest both an embrace of the spirit and the letter of the law, or promulgating both legislative and cultural change to ensure that the rights of people with disabilities are met. In attempting to understand how and if such change has happened, researchers have gathered extensive evidence since 1990. Much of this research evidence, however, remains fragmented, under-utilized, and at times inconclusive. This article presents the results of a rapid evidence review of a sample of such research that is crucial to understand the ADA’s progress. The study examines evidence about the ADA’s influence on knowledge, attitudes and perceptions about employment of people with disabilities. The research illustrates the importance of moving beyond the law to incorporate changes in knowledge about the law, perceptions of employability, and workplace culture.